THE INFLUENCE OF LEADERSHIP ETHICS AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE: PENGARUH ETIK LEADERSHIP DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Furqon (UPMI Proceeding Series, 2023)
This study aims to determine the effect of Leadership Ethics and Work Environment on Employee Performance with Job Satisfaction as Intervening Variables at the Community and Village Empowerment Service in Lubuk Pakam. The analytical method used in this research is quantitative descriptive analysis. The analytical tool used is multiple linear regression analysis using IBM SPSS version 22.0. The results of the study show that the ethical leadership significance value is 0.001 <0.05, so it can be concluded that the ethical leadership variable has a significant effect on employee performance. The work environment significance value is 0.006 <0.05, so it can be concluded that the work environment variable has a significant effect on employee performance. It is known that the significant value of the leadership ethics variable is 0.003 (<0.05) so it can be concluded that the leadership ethics variable has a significant effect on job satisfaction. It is known that the significant value of the work environment variable is 0.245 (> 0.05) so it can be concluded that the work environment variable has no significant effect on the job satisfaction variable. It is known that the direct influence of the work environment on job satisfaction is 0.206. Meanwhile, the indirect effect of the work environment through employee performance on job satisfaction is the multiplication of the beta value (work environment on employee performance) and the beta value (employee performance on job satisfaction), namely 0.342 x 0.172 = 0.058. Based on the two calculations, it is known that the direct effect is 0.559 and the indirect effect is 0.084, the direct effect is 0.206 and the indirect effect is 0.058. It can be interpreted that the indirect effect is smaller than the direct influence of leadership ethics and the work environment through employee performance does not have a significant effect on job satisfaction.